2017
DOI: 10.3389/fonc.2017.00258
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the HPV11E6 and HPV18E6 Pathways in Initiating Cellular Transformation

Abstract: Although high-risk human papillomaviruses (HPVs) are the major risk factors for cervical cancer they have been associated with several other cancers, such as head and neck and oral cancers. Since integration of low-risk HPV11 DNA has been demonstrated in esophageal tumor genomes, this study compared the effects of low-risk HPV11E6 and high-risk HPV18E6 on cellular gene expression. The HPV11E6 and HPV18E6 genes were cloned into an adenoviral vector and expressed in human keratinocytes (HaCaT) in order to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…It is thought that loss of epithelial integrity may allow HPV particles to enter and infect the basal cells [ 60 ]. Subsequently, HPV may use its oncoproteins (specifically E6 and E7) to trigger oncogenic cellular transformation through deregulation of cellular signalling pathways and deregulation of tumour suppressor genes [ 61 ]. In the present study, functional cell motility pathway was enriched in women without HR-HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that loss of epithelial integrity may allow HPV particles to enter and infect the basal cells [ 60 ]. Subsequently, HPV may use its oncoproteins (specifically E6 and E7) to trigger oncogenic cellular transformation through deregulation of cellular signalling pathways and deregulation of tumour suppressor genes [ 61 ]. In the present study, functional cell motility pathway was enriched in women without HR-HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factor binding sites, protein modifications, alterations of the DNA structure as well as methylation patterns can now be analysed and measured at the genome level [ 91 , 92 , 93 , 94 , 95 , 96 ]. Several studies including our own have identified deletions, insertions, copy number variations, splicing variants and translocations associated with certain cancers, and in so doing identified new drug targets [ 97 , 98 , 99 , 100 , 101 , 102 ]. The development of novel and unrivalled technologies, allowing genome-wide analysis, has enabled the unbiased discovery of drug targets.…”
Section: Natural Products Drug Discovery Research and Development mentioning
confidence: 99%
“…In principle, there are different ways to investigate the role of HPV oncogenes in host cell transformation. The most common approaches were either to express or to knock down E6 and/or E7 to study the changes in host transcriptome profiling (1923). In addition, available cell lines or clinical samples with different progression states were used to examine the role of either distinct HPV oncogenes or the whole viral genome in an episomal or integrated state (22, 24, 25).…”
Section: Introductionmentioning
confidence: 99%